2020
DOI: 10.31234/osf.io/sf8ez
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Einstein effect: Global evidence for scientific source credibility effects and the influence of religiosity

Abstract: People tend to evaluate information from reliable sources more favourably, but it is unclear exactly how perceivers' worldviews interact with this source credibility effect. Here, we present data from a cross-cultural study in which individuals (N = 10,195) from a religiously and culturally diverse sample of 24 countries were presented with obscure, meaningless statements attributed to either a spiritual guru or a scientist. The data indicate a robust global source credibility effect for scientific authorities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 100 publications
0
3
1
Order By: Relevance
“…We also found no effect of Source, which was surprising given that past studies have found that pseudo-profound bullshit is rated as more profound when attributed to credible or expert sources than when no source is given (Gligorić & Vilotijević, 2019;Hoogeveen et al, 2020;Ilić & Damnjanović, 2021). However, much of the bullshit that people are exposed to is encountered online (Simpson, 2019) and the way that we presented our stimuli is noticeably dissimilar to the visual formats more common to the ways in which misinformation is often presented online, particularly on social media (e.g., memes, fake news headlines, social media comments, etc.).…”
Section: Discussioncontrasting
confidence: 40%
“…We also found no effect of Source, which was surprising given that past studies have found that pseudo-profound bullshit is rated as more profound when attributed to credible or expert sources than when no source is given (Gligorić & Vilotijević, 2019;Hoogeveen et al, 2020;Ilić & Damnjanović, 2021). However, much of the bullshit that people are exposed to is encountered online (Simpson, 2019) and the way that we presented our stimuli is noticeably dissimilar to the visual formats more common to the ways in which misinformation is often presented online, particularly on social media (e.g., memes, fake news headlines, social media comments, etc.).…”
Section: Discussioncontrasting
confidence: 40%
“…The dataset provided to the analysts featured data from 10,535 participants from 24 countries collected in 2019. The data were collected as part of the cross-cultural religious replication project (see also Hoogeveen et al, 2021;Hoogeveen and van Elk, 2018). The dataset contained measures of religiosity, well-being, perceived cultural norms of religion, as well as some demographic items.…”
Section: The Datasetmentioning
confidence: 99%
“…Moreover, research showed a significant relationship between religiosity and credibility. Hoogeveen et al (2020) claimed that more people believe in a spiritual guru because they have reasonable judgments. Significantly, Said et al (2019) found that religiosity is negatively associated with fraudulence, implying that religiosity discourages fraudulent transactions.…”
Section: Relationship Between Religiosity and Credibilitymentioning
confidence: 99%